ENHANCING WRITING PROFICIENCY THROUGH MOBILE-ASSISTED LANGUAGE LEARNING (MALL): INSIGHTS AND INNOVATIONS - Zaniar, Savira; Djuwari; Afandi, Mujad Didien; Aquariza, Novi Rahmania; Authar, Nailul (English Language Teaching Methodology, 2025)
Mobile-Assisted Language Learning (MALL) improves writing proficiency through flexible, interactive, and feedback-oriented educational experiences. Mobile devices provide real-time modifications, multimedia integration, and collaborative activities such as blogging and peer review, allowing students to enhance their writing skills beyond conventional classroom limitations. Writing, a critical skill in language acquisition, requires not only mastery of vocabulary and syntax but also the ability to structure ideas and communicate effectively. However, traditional classroom instruction often lacks the immediate feedback and interactivity that modern learners need. MALL addresses these challenges by offering real-time feedback, interactive exercises, and multimedia resources that enhance the writing process. Mobile-Assisted Language Learning (MALL) promotes vocabulary enhancement and cultural understanding via real digital information. Despite obstacles like technical limitations and application choices, its capacity to promote learner-centred environments is considerable. This study investigates the role of Mobile-Assisted Language Learning (MALL) in enhancing writing skills, focussing on its advantages and obstacles, and analysing techniques to optimise its effectiveness. The findings from this research can guide optimal strategies for integrating mobile technology into language education, thereby enhancing student engagement and writing proficiency.